Evaluation of Curriculum 2013 with Context Input Process Product Model in Schools of Kediri, Indonesia - Ahid, Nur; Hidayah, Noer; Maskur, Ruhban; Purnama, Syahfitri (International Journal of Psychosocial Rehabilitation, 2020)
This study seeks to provide a comprehensive description and explanation of the implementation of the 2013 curriculum in elementary schools, junior high schools, senior high schools in the City and Kediri districts that has entered its fourth year. This research activity is an evaluation research using the Context Input Process Product (CIPP) model developed by Stufflebeam through quantitative and qualitative approaches. The context component, in general the 2013 curriculum implemented in elementary schools, junior high schools, senior high schools in the City and Kediri districts has already been understood by teachers and students. 2013 curriculum input components implemented in elementary schools, junior high schools, senior high schools in the City and Kediri districts run according to the existing format. Components of the 2013 curriculum learning process carried out in elementary schools, junior high schools, senior high schools in the City and District of Kediri, starting from the planning, implementation, and assessment (assessment), run in accordance with the existing guide format. Product components, both academic achievements and academic non-spiritual aspects, social attitudes, knowledge and student skills in elementary schools, junior high schools, high schools in the City and Kediri districts, each school varies, depending on the readiness and quality of schools, especially from human resources and infrastructure owned.